2020
DOI: 10.3390/land9090285
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Transition and Its Eco-Environmental Effects in the Beijing–Tianjin–Hebei Urban Agglomeration: A Production–Living–Ecological Perspective

Abstract: With the rapid development of urbanization and industrialization, China’s metropolitan areas have experienced dramatic transitions of land use, which has had a profound impact on the eco-environment. Accordingly, the contradictions of regional production, living, and ecological spaces have intensified. In this context, analysis of the dynamics of regional production–living–ecological (PLE) spaces has become an important entry point for studying land use transition and its eco-environmental effects, by construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 71 publications
2
81
1
Order By: Relevance
“…The expansion of land for construction led to landscape fragmentation, environmental degradation and the destruction of ecosystem services [59]. Faced with these problems and challenges, since 2012, China has proposed a shift in the spatial development model for its land from a production-space orientation to ecologicalproduction-living coordination to optimize the spatial layout of land and alleviate the contradiction between urban and rural development [22]. This is why Zhulin's ecological spatial area decreased from 2010 to 2018, while its functional suitability was significantly enhanced in this period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The expansion of land for construction led to landscape fragmentation, environmental degradation and the destruction of ecosystem services [59]. Faced with these problems and challenges, since 2012, China has proposed a shift in the spatial development model for its land from a production-space orientation to ecologicalproduction-living coordination to optimize the spatial layout of land and alleviate the contradiction between urban and rural development [22]. This is why Zhulin's ecological spatial area decreased from 2010 to 2018, while its functional suitability was significantly enhanced in this period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the natural properties of land, the classification of EPL spaces should be based on the subjective land-use intentions of the actors [22]. Among these, production space refers to a land-use system that provides a material space carrier for human production and business activities [44].…”
Section: Identification and Classification Of Epl Spacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the production-living-ecological space helps optimizing space, governing resources and environment, and promoting ecological development. Research has revealed that the distribution of the production-living-ecological space strongly correlates with the living quality, utilization of space, and the ecological environment [33][34][35] . Currently, only a few studies have revealed the correlation between the production-livingecological space and LST, and the correlation degree remains unknown.…”
mentioning
confidence: 99%